Assessment of water quality in Bangon River, Palo, Leyte using biomarkers in zebrafish (Danio rerio) embryos - Pedrosa, Milkah Agatha Dana C.; Parilla, Richard B. (2022)
Rivers are important freshwater biomes that biomes that provide multiple ecosystem services. Diverse flora and fauna further depend on these ecosystems for sustenance and survival. However, the increased anthropogenic activities have greatly deteriorated their water quality. The Bangon River is a 38-km-long river hat traverses the agricultural and residential areas of Palo before draining into the Leyte Gulf. To determine its current water quality, physicochemical analysis and modified Zebrafish Embryo Toxicity (ZFET) Test were conducted. The physicochemical analysis showed that the Bangon River met most of the criteria for a class C river. However, the ammonia concentration in all sampling points exceeded the standard set by the DENR. Subsequently, the ZFET test resulted in significantly higher lethality and abnormality rates in the downstream sampling points with significantly lower hatching success and survival rates. In comparison, the upstream sampling points obtained low lethality and abnormality rates with high hatching and survival rates. These results can be attributed to the high ammonia concentration obtained in the physicochemical analysis and the presence of point and nonpoint source pollution along the river such as direct entry of domestic wastewater. With these results, it was determined that Bangon River waters pose a significant threat to zebrafish embryos. These findings could be used as baseline information for a more comprehensive assessment of the river's quality and an evaluation of existing rehabilitation strategies.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.